Caitro Soto: “De canto, baile y cadenas”. Testimonio y cultura Afroperuana - Carazas, Milagros (2018)
Analyze the work De cajón Caitro Soto. El duende de la música afroperuana (1995), a book dedicated to the artist Carlos Soto de la Colina (1934-2004). It explores its history of life, oral tradition, the musical genres Afro-Peruvian. Reflect on the song Peruvian and its content.